2020
DOI: 10.3389/fnbeh.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Pyriproxyfen Exposure Impairs Cognitive Parameters and Alters Cortisol Levels in Zebrafish

Abstract: Pyriproxyfen is one of the most used larvicides and insecticides; it acts as an analog of juvenile insect hormone (a growth regulator). It is highly toxic during all stages of mosquito development, suppresses metamorphosis, and interferes in insect reproduction and proliferation. Pyriproxyfen and its main metabolite have been shown to affect brain development in rodents. This compound is employed mainly to eliminate outbreaks of the genus Aedes, even in potable water. Despite the increasing number of toxicolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
(94 reference statements)
0
9
1
Order By: Relevance
“…However, no significant effects on distance swam, velocity, and anxiety-like behavior were seen in zebrafish after administration of 0.125, 0.675, and 1.75 mg L −1 Pyr. Although, disruptions of inhibitory avoidance memory were present at each concentration [ 21 ]. A single administration of Pyr at 10 and 100 µg L −1 during 21 days caused endocrine and reproductive alterations in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant effects on distance swam, velocity, and anxiety-like behavior were seen in zebrafish after administration of 0.125, 0.675, and 1.75 mg L −1 Pyr. Although, disruptions of inhibitory avoidance memory were present at each concentration [ 21 ]. A single administration of Pyr at 10 and 100 µg L −1 during 21 days caused endocrine and reproductive alterations in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Fip, ecotoxicological data for Pyr effects on fish is still very limited. Several studies demonstrated that Pyr may lead to developmental deformities, changes in heart size, DNA damage, high levels of ROS (reactive oxygen species), enzyme inhibition, erratic swimming, and lethargy in Xiphophorus maculatus , Danio rerio , and Haplosternum littorale [ 17 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to OTC, FF, and OTC + FF was carried out as follows. Zebrafish larvae at 4 dpf were exposed to OTC (2, 10, 20, and 100 mg/L; CAS number 79-57-2), FF (0.01, 0.05, 2, and 10 mg/L; CAS number 73231-34-2) or OTC+ FF (10 mg/L + 10 mg/L) for 96 h. The FF was diluted in Dimethyl sulfoxide (DMSO; CAS number 67-68-5) at a final concentration of less than 0.1% (Gusso et al, 2020;Nery et al, 2014).…”
Section: Antibiotics Exposurementioning
confidence: 99%
“…In this sense, it is essential to study the role of antibiotics using zebrafish, a useful animal model to understand the mechanisms behind these disorders. In recent decades, zebrafish have been used for the development of studies in various areas, such as pharmacology (Idalencio et al, 2015;Petersen et al, 2021) toxicology (Bridi et al, 2017;Gusso et al, 2020), and endocrinology (Gaspary et al, 2018;Giacomini et al, 2015). This model has gained space for studies in neurosciences, contributing to a better understanding of brain function and dysfunctions and also to pharmacological modulation (Grossman et al, 2011;Müller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas none of these studies investigated the sublethal effects of pyriproxyfen exposure on parental care, a few studies demonstrated that pyriproxyfen exposure at the larval stage can alter other important behaviours in aquatic vertebrates and honeybees. For instance, pyriproxyfen exposure impaired inhibitory avoidance memory in Zebrafishes (Gusso et al 2020) and swimming performances and prey capture abilities in mosquitoes (Caixeta et al 2016), while the exposure of honeybee larvae produces adults with behavioural alterations, such as a lower expression of brood care and a higher rejection by nestmates (Fourrier et al 2015).…”
Section: Introductionmentioning
confidence: 99%